Efficient Solar Air Heater Absorber Plate for Crop Drying Application - Gyaneshwar Sanodiya, (Indian Journal of Agriculture Engineering (IJAE), 2024)
Solar air heaters are commonly placed on farms to provide heat during the drying of croplands. This practice has been studied to see if solar air heaters can provide adequate heat to support the harvesting and drying of crops. The study revealed that solar air heaters can provide sufficient heat to support the drying of croplands and the harvesting of grain. However, solar air heaters are more efficient when their air flow and thermal capacity are equal. To be more economical, they should be designed with more efficient components such as reflectors and ducting systems. The air flow and the thermal capacity of the solar air are also affected by the duct system’s low heat transfer coefficient. This can be increased by taking advantage of the air’s restricted thermal capacity. Active and passive approaches can also be used to increase the HT coefficient of solar air heaters. In most cases, this method is more cost-effective than using an absorber plate. In most cases, the use of an active or passive approach can increase the air flow and the HT coefficient of solar air heaters. This CFD study focused on the link between the roughness element for solar air heater ducts and the HT capacity of the system.